Evaluation of Lactiplantibacillus plantarum CRS 33 to therapeutic effects on a murine model of Escherichia coli-induced endometritis - Liu, Mingchao; Wen, Xiangfu; Feng, Mingque; Sun, Yan; Feng, Xiaowei; Jin, Tianxiong; Liu, Bei; Muhammad, Shahid; Liu, Kangping; Cheng, Jia; Li, Jianguo (Frontiers in Veterinary Science, 2025)
IntroductionBovine endometritis is a common postpartum uterine disease in dairy cows that is traditionally treated with antibiotics. However, excessive antibiotic use can lead to antimicrobial resistance and treatment failure. Lactiplantibacillus plantarum CRS33, a novel probiotic strain isolated from the uterus of a healthy cow, exhibits strong antibacterial potential. This study aimed to investigate the probiotic characteristics of Lactiplantibacillus plantarum CRS33 through whole-genome sequencing and to evaluate its anti-inflammatory effects in a mouse model of Escherichia coli–induced endometritis.MethodsWhole-genome sequencing was performed to identify genes related to antibacterial, anti-inflammatory, and immune-regulatory activities, and to confirm the absence of antibiotic resistance and virulence genes. Female mice were induced with Escherichia coli endometritis and treated with Lactiplantibacillus plantarum CRS33 at a dose of 1 × 10⁹ CFU/mL. Uterine morphology, wet weight index, inflammatory cell infiltration, cytokine levels (IL-6, IL-1β, IL-8, TNF-α), and uterine microbiota composition were analyzed.ResultsGenomic analysis revealed that Lactiplantibacillus plantarum CRS33 contains multiple functional genes related to antimicrobial, anti-inflammatory, and immune-modulatory pathways and lacks antibiotic resistance or pathogenic determinants. Treatment with Lactiplantibacillus plantarum CRS33 significantly alleviated uterine inflammation, reduced the wet weight index (p < 0.05), and improved histopathological lesions. It also decreased pro-inflammatory cytokine levels and inflammatory cell infiltration, while enhancing microbial diversity and increasing the abundance of beneficial bacterial taxa.DiscussionLactiplantibacillus plantarum CRS33 demonstrates strong anti-inflammatory and microbiota-regulating properties in Escherichia coli–induced endometritis, highlighting its potential as a safe and effective probiotic alternative to antibiotics. Further validation in dairy cows is warranted to confirm its therapeutic potential under practical conditions.